State and authoritarianism in Latin America: The conceptions of Ruy Mauro Marini and Guillermo O’Donnell - Neves, Fernando (2022)
The implementation of authoritarian regimes in Latin America in the 60’s and 70’s had a wide repercussion on research and debates in social sciences. The works of Ruy Mauro Marini and Guillermo O’Donnell on Latin American state and authoritarianism bring together some of these impacts on the production of social knowledge, in view of their commitment to the destiny of the societies in which they were inserted, although from distinct, heterogeneous, and sometimes conflicting theoretical principles and political perspectives. This theoretical opposition gains relevance today, given the return of authoritarian ideas and practices in our social realities.